Antibiotic Pharmacokinetic/Pharmacodynamic Considerations in the Critically Ill (Springer Singapore, 2018)
This book provides unique insights into the issues that drive modified dosing regimens for antibiotics in the critically ill. Leading international authors provide their commentary alongside a summary of existing evidence on how to effectively dose antibiotics. Severe infection frequently necessitates admission to the intensive care unit (ICU). Equally, nosocomial sepsis often complicates the clinical course in ICU. Early, appropriate application of antibiotic therapy remains a cornerstone of effective management. However, this is challenging in the critical care environment, given the significant changes in patient physiology and organ function frequently encountered. Being cognisant of these factors, prescribers need to consider modified dosing regimens, not only to ensure adequate drug exposure, and therefore the greatest chance of clinical cure, but also to avoid encouraging drug resistance.